The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1121/1.4896745
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic-emission-based medial-olivocochlear reflex assays for humans

Abstract: Otoacoustic emission (OAE) tests of the medial-olivocochlear reflex (MOCR) in humans were assessed for viability as clinical assays. Two reflection-source OAEs [TEOAEs: transient-evoked otoacoustic emissions evoked by a 47 dB sound pressure level (SPL) chirp; and discrete-tone SFOAEs: stimulus-frequency otoacoustic emissions evoked by 40 dB SPL tones, and assessed with a 60 dB SPL suppressor] were compared in 27 normal-hearing adults. The MOCR elicitor was a 60 dB SPL contralateral broadband noise. An estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 49 publications
(81 reference statements)
15
74
0
1
Order By: Relevance
“…Therefore, the change in CEOAE level due to the presence of IAS and CE-block could arise from transient OAEs and potential SSOAEs caused by IAS and CEblock clicks. SSOAEs were not measured in the current study, however, Marshall et al 35 reported that presence of SSOAEs in their chirp-evoked OAE sample did not affect the observed of MOC inhibition between participants withand without-SSOAEs. Also, considering that the amount of MOC inhibition caused by both IAS and CAS is statistically the same and numerically very similar, it is unlikely that the SSOAEs and transient OAEs evoked by IAS/CE-block clicks, if present, had a large effect on the observed MOC inhibition in the current study.…”
Section: Caveatsmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the change in CEOAE level due to the presence of IAS and CE-block could arise from transient OAEs and potential SSOAEs caused by IAS and CEblock clicks. SSOAEs were not measured in the current study, however, Marshall et al 35 reported that presence of SSOAEs in their chirp-evoked OAE sample did not affect the observed of MOC inhibition between participants withand without-SSOAEs. Also, considering that the amount of MOC inhibition caused by both IAS and CAS is statistically the same and numerically very similar, it is unlikely that the SSOAEs and transient OAEs evoked by IAS/CE-block clicks, if present, had a large effect on the observed MOC inhibition in the current study.…”
Section: Caveatsmentioning
confidence: 67%
“…However, a recent study tested the influence of SSOAEs on MOC inhibition of CEOAEs, and found no difference in the strength of MOC inhibition between individuals with SSOAEs and individuals with no SSOAEs. 35 This report suggests that the presence of SSOAE in the CEOAE spectrum may not significantly influence the observed MOC inhibition. Most studies that investigate the MOC using clicks have used a 50 Hz click presentation rate as a safe cut-off to avoid evoking ipsilateral MOC activity.…”
Section: A Optimal Click Presentation Ratementioning
confidence: 90%
“…Each participant was tested for the presence of spontaneous OAEs (SOAEs) using the synchronized SOAE technique (reported in Marshall et al, 2014). Briefly, responses to 1000 clicks at 55 dB peSPL, presented every 64 ms, were recorded in a linear mode.…”
Section: Recording Of Ceoaesmentioning
confidence: 99%
“…For instance, CEOAE latency can be used to objectively estimate cochlear tuning in the pediatric population, in whom psychophysical tuning curves may be difficult to obtain (Moleti and Sisto, 2003;Moleti et al, 2008). The latency can be applied to accurately characterize the efferent effects on cochlear mechanisms (Francis and Guinan, 2010) and compute a vector metric to index efferent reflex (Abdala et al, 2013;Marshall et al, 2014;Mishra and Abdala, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…OAE-based measurements have revealed characteristics of MOC reflex tuning (e.g., Veuillet et al 1991; Chéry-Croze et al 1993; Lilaonitkul and Guinan 2007; Zhao & Dhar, 2012), strength (e.g., Backus & Guinan, 2007; Marshall et al, 2014), and the mechanism’s possible involvement in directed auditory attention (e.g., Froehlich et al, 1993; de Boer & Thornton, 2007; Garinis et al, 2011) or listening in noise tasks (e.g., Giraud et al, 1997; Kumar & Vanaja, 2004; de Boer & Thornton, 2008; Smith & Cone, 2015; de Boer et al, 2012). However, a major limitation of this approach is that OAEs are insensitive to MOC reflex effects on the neural ensembles that mediate human hearing, and the functional consequences of this mechanism remain unclear.…”
Section: Introductionmentioning
confidence: 99%